2010
DOI: 10.1158/1535-7163.mct-09-1061
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fatty Acid Synthase Suppresses c-Met Receptor Kinase and Induces Apoptosis in Diffuse Large B-Cell Lymphoma

Abstract: Fatty acid synthase (FASN), the enzyme responsible for de novo synthesis of fatty acids, has emerged as a potential therapeutic target for several cancers; however, its role in diffuse large B-cell lymphoma (DLBCL) has not been fully elucidated. In this study, we investigated the role of FASN in a large series of DLBCL tissues in a tissue microarray (TMA) format followed by in vitro studies using DLBCL cell lines. FASN was found to be expressed in 62.6% DLBCL samples and was seen in highly proliferative tumors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 39 publications
6
34
1
2
Order By: Relevance
“…FASN inhibition has also been described as a sensitizer for cisplatin treatment in mice xenografted with human ovarian cancer cells (30). In fact, FASN is highly expressed across a wide range of human tumor types where its inhibition either induces apoptosis and/or synergizes with cytotoxic agents (31)(32)(33)(34)(35)(36)(37)(38). Consistent with these data, we show that inhibition of FASN with short hairpin RNAs also sensitized our CDH1-deficient cells to cisplatin treatment.…”
Section: Discussionsupporting
confidence: 86%
“…FASN inhibition has also been described as a sensitizer for cisplatin treatment in mice xenografted with human ovarian cancer cells (30). In fact, FASN is highly expressed across a wide range of human tumor types where its inhibition either induces apoptosis and/or synergizes with cytotoxic agents (31)(32)(33)(34)(35)(36)(37)(38). Consistent with these data, we show that inhibition of FASN with short hairpin RNAs also sensitized our CDH1-deficient cells to cisplatin treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies by many groups have shown that FASN overexpression or inhibition modulates Akt as well as other drivers of oncogenic signaling that include c-Met, ERBB2, EGFR, and Wnt-b-catenin (Ventura et al, 2015, Coleman et al, 2009, Uddin et al, 2010, Hu et al, 2016, Puig et al, 2011, Vazquez-Martin et al, 2008, Bollu et al, 2015). Our observation that combining TVB-3166 or TVB-3664 with taxane treatment increased efficacy in several tumor models of diverse origin and genetic features suggests the primary mechanism is fundamental to tumor cell biology and the taxane mechanism of action such as tubulin palmitoylation, expression, and the disruption of microtubule function; however, complementary mechanism may play an important role in a manner that is dependent upon tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…It is recently reported that fatty acid synthase (FAS) inhibition triggered caspase-dependent apoptosis and suppressed the expression of c-MET in DLBCL cell lines [32]. Pharmacological FAS blockade might result in rapid changes in the lipid composition of the tumor cell membrane, which could impair a correct cellular localization of c-MET [33]. Moreover, FAS inhibition may cause an imbalance in the membrane phospholipids levels, which may result in decreased c-MET membrane localization and activation [34].…”
Section: The Expression/activation Of Hgf/c-met In Different Types Ofmentioning
confidence: 99%